Analisis Kebutuhan Video Tutorial untuk mahasiswa pada Mata Kuliah Media Foto - Aswan, Dedy (Jurnal Ilmiah Wahana Pendidikan, 2024)
multimedia integration, mainly video tutorials, plays a crucial role in education. This study investigates the needs of students regarding video tutorials in the context of the Media Photography course at Universitas Negeri Makassar (UNM). An online survey involving 50 students from the Technology Education Program examined preferences for learning, challenges in understanding course materials, and expectations for video tutorials. The findings reveal that 80% of students prefer video tutorials, valuing their visual demonstrations and practical examples. Despite this preference, students need help understanding lighting concepts, complex camera settings, and photo editing techniques. They desire comprehensive, engaging, interactive video tutorials covering theoretical concepts and providing practical demonstrations. The study emphasizes the importance of aligning instructional design with student preferences and addressing specific learning challenges. Educators are encouraged to integrate tailored video tutorials into the curriculum to improve learning outcomes and student engagement